The Impact of Teaching Experience on Professors’ Use of ICTs in the Teaching Process - Hicham Laabidi (TRANSBAHASA, 2022)
Technology advancements have made learning more exciting for pupils of all levels. Many studies have shown that using current technology in the classroom benefits both teachers and students. It has fueled their drive to learn more using these new instruments. Thus, schools and other educational institutions have recognized the value of using computers to teach. This paper intends to investigate the influence of teaching experience and teachers’ age on the implementation of ICTs in the classroom. The data were analyzed using descriptive means and standard deviations. To assess the impact of teaching experience on computer use for pedagogical purposes, inferential statistics were used. Based on the independent variable of teaching experience, the results showed statistically significant variations in instructors' usage of new technologies in education., F (4,158) = 20.279, p < 0.05. The current study is highly significant in the sense that it is expected to come up with important findings with regard to the infusion and implementation of information technology in higher education. It provides significant knowledge that can be of great value to both researchers and professors in Morocco and in various parts of the world.